Influence of Social Media Marketing Strategies and Best Practices on E-Satisfaction And E-Loyalty - Suzette Colonia Quico (Faculty of Economics, Universitas Sriwijaya, 2023)
This study investigated hotels' social media marketing strategies in Davao Region. Also, it determined the perceived effectiveness of the social media marketing used by the selected hotels' level of e-satisfaction of tourists using social media marketing by selected hotels. This study used a descriptive research design since it aimed to explain and interpret the findings gathered from the quantitative data. There were 455 respondents for the quantitative data and eight (8) respondents for the qualitative data. Instruments used in the study were an adapted survey questionnaire and an in-depth interview utilizing the research guide questions. The study participants were purposively selected, and the questionnaires were distributed equally. This study analyzed the statistical data using the Frequency, Weighted Median, Kruskal-Wallis, Spearman's Rank-Order Correlation, and Multiple Regression Analysis. Data revealed that social media is one of the most cost-efficient digital marketing methods; Facebook is the most prevalent Social Networking Site (SNS) used by hotels and use third-party booking sites to support the hotel's revenue. Moreover, findings showed that selected hotels implemented a high level of effectiveness of social media, a high level of customers' e-satisfaction on social media, and a high level of e-loyalty of hotels' customers on social media marketing strategies by hotels. Thus, the result clarified that compared to social media marketing, e-satisfaction, as a factor in general, was influential in igniting e-loyalty. Lastly, three (3) best practices were identified from the participants: innovation, customer engagement, and accessibility.